Making non-state actors accountable for violations of socio-economic rights: a case study of transnational corporations in the African context - Van Reenen, Tobias (University of Pretoria, 2006)
Prepared under the supervision of Professor Tobias van Reenen at the Faculty of Law, University of the Western Cape, Cape Town, South Africa